Time and Emotion During Lockdown and the Covid-19 Epidemic: Determinants of Our Experience of Time? - Martinelli, Natalia; Gil, Sandrine; Belletier, Clément; Chevalère, Johann; Dezecache, Guillaume; Huguet, Pascal; Droit-Volet, Sylvie (Frontiers in Psychology, 2021)
To fight against the spread of the coronavirus disease, more than 3 billion people in the world were confined. Although the lockdown is an efficient solution, it has different psychological consequences which have not yet been fully measured. During the lockdown period in France (April 2020), we conducted two surveys on two large panels of participants to examine how the lockdown disrupted their relationship with time and what this change in the experience of time means. Numerous questions were asked about the time experience but also the nature of life during the lockdown, the emotions felt, boredom, the activities performed, sleep quality, and the daily rhythm. The participants also completed a series of self-reported scales used to assess depression, anxiety and impulsivity. The results showed that time seemed to pass very much more slowly during the lockdown compared to before. This feeling of a slowing down of time has little to do with living conditions during the lockdown and individual psychological characteristics. The main predictor of this time experience was boredom, partly mediated by the lack of activity. The feeling of being less happy and the disturbance to sleep also explained this specific experience of time, albeit to a lesser extent.